2018
DOI: 10.1007/s13762-018-1802-z
|View full text |Cite
|
Sign up to set email alerts
|

A study to reduce atmospheric emissions of an existing natural gas dehydration plant using multiple thermodynamic models

Abstract: Using Aspen Plus, operating parameters of an existing triethylene glycol natural gas dehydration plant including the solvent circulation rate, stripping gas flow rate, regenerator reboiler duty, solvent temperature, absorber (contactor) pressure, flash unit pressure and regenerator pressure were optimized to reduce BTEX, VOCs and CO 2 emissions. The plant consists of an absorber, a flash tank, a stripper and a regenerator. Two thermodynamic models including PRMHV 2 and PSRK were utilized for this plant. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Amouei Torkmahalleh et al [38] observed that the infuence of the reboiler duty, which is related to the regenerator temperature, is insignifcant with a slight increase in BTEX emissions observed with increasing the regeneration temperature. However, it is noted that at lower reboiler duty values, the infuence of the reboiler duty on BTEX emissions is more signifcant.…”
Section: Efect Of Teg Regeneratormentioning
confidence: 99%
See 2 more Smart Citations
“…Amouei Torkmahalleh et al [38] observed that the infuence of the reboiler duty, which is related to the regenerator temperature, is insignifcant with a slight increase in BTEX emissions observed with increasing the regeneration temperature. However, it is noted that at lower reboiler duty values, the infuence of the reboiler duty on BTEX emissions is more signifcant.…”
Section: Efect Of Teg Regeneratormentioning
confidence: 99%
“…Tey also found that the stripping gas fow rate signifcantly impacts VOC emissions. Amouei Torkmahalleh et al [38] examined the impact of solvent circulation rate, reboiler heat duty, stripping gas circulation rate, and lean TEG temperature on BTEX, VOCs, and CO2 emissions. Teir results showed that increasing solvent circulation rate decreases dry gas moisture content to some extent, and if a solvent fow rate up to 9.25 GPM is used, the moisture content starts rising.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that when the flow rate of nitrogen is increased to 400 kg h −1 , the concentration of the lean liquid can reach 0.999 wt%, the moisture content in the dry gas is reduced to below 1 ppm, but the loss of TEG increases to about 2.2 kg h −1 . Amouei Torkmahalleh et al [ 19 ] used two methods for sensitivity analysis in Aspen Plus. The first one is single factor sensitivity analysis, which is more intuitive to study the influence of the parameter disturbance on the process by controlling a single variable; the second one is sensitivity analysis is performed for a given parameter when all other parameters are optimal.…”
Section: Introductionmentioning
confidence: 99%